1994
DOI: 10.1063/1.111758
|View full text |Cite
|
Sign up to set email alerts
|

Heterojunction fabrication by selective area chemical vapor deposition induced by synchrotron radiation

Abstract: We have fabricated a B5C, boron-carbide/Si(111) heterojunction diode by the synchrotron radiation-induced decomposition of orthocarborane. This diode can be compared with similar boron-carbide/Si(111) heterojunction diodes fabricated by plasma enhanced chemical vapor deposition. The synchrotron radiation induced chemical vapor deposition is postulated to occur via the decomposition of weakly chemisorbed species and the results suggest that ‘‘real-time’’ projection lithography (selective area deposition) of bor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
1

Year Published

1994
1994
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 24 publications
1
62
1
Order By: Relevance
“…In contrast, a double diffraction peak at 43.7° and 44.2° is observed in Fig. 3b for undoped B 5 C [1,8,27]. The calculated d spacing for the doublet diffraction peak is 2.03 Å and 1.87 Å, respectively, which is 5%-10% smaller than for the P-doped alloy.…”
Section: Phosphorus-doped B 5 C Inmentioning
confidence: 82%
“…In contrast, a double diffraction peak at 43.7° and 44.2° is observed in Fig. 3b for undoped B 5 C [1,8,27]. The calculated d spacing for the doublet diffraction peak is 2.03 Å and 1.87 Å, respectively, which is 5%-10% smaller than for the P-doped alloy.…”
Section: Phosphorus-doped B 5 C Inmentioning
confidence: 82%
“…Such heterogeneous decomposition, while leading to closure of the HOMO-LUMO gap, would also be accompanied by very large photoemission peak widths that are not observed, as noted earlier. Thus the prior explanations 15,19 of the photoemission binding energy shifts, for orthocarborane, as due to HOMO-LUMO gap closure are incorrect.…”
Section: Fig 2 ͑Color͒mentioning
confidence: 98%
“…A wealth of characterization suggests that the resulting boron-carbide semiconductor materials, from both electron beam and synchrotron radiation assisted decomposition, are very similar. 15,16 During decomposition, the exopolyhedral hydrogen is removed from the carborane molecules.…”
mentioning
confidence: 99%
“…This achievement builds upon the recent success in construction of boron-carbide/nSi͑111͒ heterojunction diodes. 5,6 We have demonstrated that boron-carbide/Si͑111͒ heterojunction diodes can be fabricated from closo-1,2,-dicarbadodecaborane (C 2 B 10 H 12 ; orthocarbonane͒ by using synchrotron radiation-induced chemical vapor deposition ͑SR-CVD͒ 5,6 and plasmaenhanced chemical vapor deposition ͑PECVD͒. 2,3,5-7 Pure boron films also had been deposited on silicon from nidodecaborane (B 10 H 14 ; decaborane͒ by using SR-CVD.…”
Section: ͓S0003-6951͑96͒00311-8͔mentioning
confidence: 99%